Effect of mood and anxiety disorders on health care utilization in multiple sclerosis. (August 2021) - Marrie, Ruth Ann; Walld, Randy; Bolton, James M; Sareen, Jitender; Patten, Scott B; Singer, Alexander; Lix, Lisa M; Hitchon, Carol A; El-Gabalawy, Renée; Katz, Alan; Fisk, John D; Marriott, James J; et al.
Background: Little is known about the effects of changes in the presence or absence of psychiatric disorders on health care utilization in multiple sclerosis (MS). Objective: To evaluate the association between "active" mood and anxiety disorders (MAD) and health care utilization in MS. Methods: Using administrative data from Manitoba, Canada, we identified 4748 persons with MS and 24, 154 persons without MS matched on sex, birth year, and region. Using multivariable general linear models, we evaluated the within-person and between-person effects of any "active" MAD on annual physician visits, hospital days, and number of drug classes dispensed in the following year. Results: Annually, the MS cohort had an additional two physician visits, two drug classes, and nearly two more hospital days versus the matched cohort. Individuals with any MAD had more physician visits, had hospital days, and used more drug classes than individuals without a MAD. Within individuals, having an "active" MAD was associated with more utilization for all outcomes than not having an "active" MAD, but the magnitude of this effect was much smaller for visits and drugs than the between-person effect. Conclusion: Within individuals with MS, changes in MAD activity are associated with changes in health services use.